A PFC Rectifier Based EV Charger for Harmonic Reduction. Issue 4 (2019) - Tiwary, Anyuti; Singh, Mukesh; Mishra, S.
Abstract: The current Indian scenario has marked adoption of Electric Vehicle (EV) to eradicate the atmosphere ′ s carbon footprint. However, the inclusion of nonlinear EV charger offers catastrophic effects to battery ′ s and EV ′ s circuitry. The AC-DC conversion of energy through conventional rectifier leads to the generation of large inrush current and obnoxious spikes in the input current. Moreover, the repercussions of interference of injected harmonics may be witnessed in the poor efficiency and degradation of the EV charger ′ s elements. Henceforth, the resultant low power factor and exaggerated total harmonic distortion (THD) makes it obvious to integrate a Power Factor Correction (PFC) circuit at the initial stage. Thus, an Orcad Pspice simulated PFC rectifier model has been proposed that eliminates the undesirable harmonics, hence, empowering the power factor. This is achieved by developing a sinusoidal input inductor current in phase with the input voltage waveform. The model adopts an easy control by using Critical Conduction Mode (CrCM) technique under which the switching operation takes place at zero as well as peak of the current waveform. Moreover, the circuit inculcates a closed loop strategy where the generated error at voltage sensing, current sensing, programmed and reference current waveform comparison is evaluated. Thus, the examination of achieved results explains the accurate working of model and realization of unity power factor.